Wanderings through the Garhwal Himalaya - Saili, Ganesh (New Delhi, 2017)
This book is a delightful collection of introspective essays on the Garhwal Himalaya and life around it. The author draws from his memories of being brought up in the mountains, pictures that linger like a waft of sweet perfume on a breezy afternoon. The book is a living tribute to the large-hearted sons of the soil, who, down the ages, have yoked the hills together, through thick and thin, good times and bad times, have laughed at the thunder and mocked the skies, have left for the plains only to return, again and again, to the call of the mountains.
Keywords: Saili, Ganesh - Travel - India - Garhwal